Short-term results of curcumin, quercetin, hyaluronic acid and chondroitin sulfate (Ialuril Soft Gels®) in the management of chronic prostatitis/primary prostate pain syndrome: a single-center prospective study - Iacovelli, Valerio; Vittori, Matteo; Carilli, Marco; Cipriani, Chiara; Signoretti, Marta; Antonucci, Michele; Petta, Filomena; Filippi, Beatrice; Di Giovanni, Giulia; Maiorino, Francesco; Saccà, Filippo Antonino Maria; Stella, Giuseppe; et al. (Frontiers in Surgery, 2025)
Aim of the studyManagement of Chronic Prostatitis/Primary Prostate Pain Syndrome (CP/PPPS) is challenging and characterized by conflicting results. This study aimed to evaluate the efficacy of a food supplement based on Curcumin, Quercetin, Hyaluronic Acid and Chondroitin Sulfate (Ialuril Soft Gels®) in CP/PPPS treatment.Materials and methodsData of consecutive male patients who referred to our Institution for CP/PPPS were prospectively collected between Oct-2022 and Jan-2023. Patients with maximum flow rate <15 ml/s, post-void residual >150 ml and/or previous prostate surgery were excluded. Variables including age, body mass index (BMI), prostate volume (PVol) and serum prostate specific antigen (PSA) were collected. Patients were asked to fulfil standardized questionnaires to assess severity of pain, lower urinary tract symptoms (LUTS) and erectile function, including Symptom Severity Index (SSI), Symptom Frequency Questionnaire (SFQ), National Institutes of Health Chronic Prostatitis Symptom Index (NHI/CPSI) (pain and LUTS domains), International Prostate Symptom Score (IPSS) and Quality of Life score (IPSS-QoL), and International Index of Erectile Function (IIEF-5). Changes in standardized questionnaires were evaluated at baseline, 30- and 90-days after enrolment. Patients were administered 2 gelcaps of Ialuril Soft Gels® (curcumin 200 mg, quercitin 200 mg, hyaluronic acid 100 mg, chondroitin sulfate 200 mg) once a day for 60 days.ResultsTwenty patients were analysed. Baseline features were age [median 50 years (IQR 46–51)], BMI [24.2 (22.8–28.3)], PVol [42 ml (30–52)], PSA [1.0 ng/ml (0.8–1.8)], SSI [54 (27–55)], SFQ [20 (13–26)], NHI/CPSI [pain domain 10 (8–13); LUTS domain 7 (4–8)], IPSS [13 (10–18)], IPSS-QoL [3 (2–3)] and IIEF-5 [17 (14–22)]. SSI and SFQ scores showed statistically significant differences both at 30- [SSI 45 (22–49), p < 0.001; SFQ 16 (11–20), p = 0.035] and 90-days [SSI 33 (17–42), p < 0.001; SFQ 13 (9–16), p < 0.001]. IPSS and NHI/CPSI pain and LUTS domains showed statistically significant differences at 30-days [IPSS 12 (10–13), p = 0.002; NHI/CPSI pain domain 6 (5–9), p < 0.001; NHI/CPSI LUTS domain 7 (2–9), p = 0.033, respectively], but not at 90-days (all p > 0.05). IPSS-QoL and IIEF-5 scores did not report any statistically significant difference during follow-up (p = 0.12 and p = 0.23, respectively). No adverse events were recorded.ConclusionsIaluril Soft Gels® seems to be effective in reducing the severity of pain and urinary symptoms in CP/PPPS patients at short-term follow-up.